2011
DOI: 10.3390/e13101746
|View full text |Cite
|
Sign up to set email alerts
|

Projective Power Entropy and Maximum Tsallis Entropy Distributions

Abstract: We discuss a one-parameter family of generalized cross entropy between two distributions with the power index, called the projective power entropy. The cross entropy is essentially reduced to the Tsallis entropy if two distributions are taken to be equal. Statistical and probabilistic properties associated with the projective power entropy are extensively investigated including a characterization problem of which conditions uniquely determine the projective power entropy up to the power index. A close relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 25 publications
0
32
0
Order By: Relevance
“…Definition 1 [Fujisawa and Eguchi (2008), Cichocki and Amari (2010), Eguchi, Komori and Kato (2011)]. For f, g ∈ M, define the γ-divergence D γ (· ·) and γ-cross entropy C γ (· ·) as follows:…”
mentioning
confidence: 99%
“…Definition 1 [Fujisawa and Eguchi (2008), Cichocki and Amari (2010), Eguchi, Komori and Kato (2011)]. For f, g ∈ M, define the γ-divergence D γ (· ·) and γ-cross entropy C γ (· ·) as follows:…”
mentioning
confidence: 99%
“…It is shown that classes of nonlinear N-dimensional Fokker-Planck equations are connected to a single entropic form and emphasis is given to the class of equations associated to Tsallis entropy, in both cases of the standard and generalized definitions for the internal energy. Finally, Eguchi, Komori and Kato [10] discuss a one-parameter family of generalized cross entropy between two distributions with the power index, called the projective power entropy which is reduced to the Tsallis entropy if two distributions are taken to be equal. They investigate statistical and probabilistic properties associated with the projective power entropy, including a characterization problem of which conditions uniquely determine the projective power entropy up to the power index.…”
mentioning
confidence: 99%
“…See [35,36] for the detailed discussion [37,38] for the discussion on group invariance. Thus, if β > 0, then the maximum β-power entropy distribution has a compact support…”
Section: Maximum Entropy Distributionmentioning
confidence: 99%